A Conversation with Gayatri Chakravorty Spivak: Politics and the Imagination. - Sharpe, Jenny (Signs: Journal of Women in Culture & Society)
Interviews feminist leader Gayatri Chakravorty Spivak on the effect of imaginative power of corporate globalization on feminism. Definition of globalization; Development of feminism in third world countries; Cultural difference between Asians and Americans.